Penilaian Pembelajaran Bahasa Indonesia di Kota Bandung pada Masa Pandemi Covid-19 - Haris Santosa Nugraha; Yeti Mulyati; Vismaia S Damaianti (Universitas Pendidikan Indonesia, 2022)
This study aims to describe the process of assessing Indonesian language learning in the city of Bandung during the Covid-19 pandemic. The research method used is a descriptive method of the Indonesian language learning assessment process. The research subjects were Indonesian high school teachers in the city of Bandung who were selected through a random sampling technique. Data collection was carried out using a questionnaire, observation, and interview techniques which were analyzed through the stages of reduction, display, and conclusion of the data. The results of this study describe three things as follows. First, during the pandemic, the assessment of Indonesian high school learning in Bandung City has implemented an assessment of Indonesian learning by utilizing digital technology. Second, the role of digital technology in assessment during this pandemic is very large so that Indonesian language learning in Bandung City can continue to run either as a supplement, complement, or substitution. Third, the ability of teachers to use digital technology in the assessment is quite good, supported by expertise in understanding and using digital technology, both hardware, software, and networks. Fourth, the assessment technique is carried out by utilizing digital technology in both knowledge test techniques and skills tests. Fifth, the problems that arise during the assessment of Indonesian language learning during the pandemic include the teacher paradigm in conducting online assessments, the ability of educators to utilize technology, and the limitations of online learning equipment.